2018
DOI: 10.1111/cmi.12839
|View full text |Cite
|
Sign up to set email alerts
|

Pleiotropic effects of the histone deacetylase Hos2 linked to H4-K16 deacetylation, H3-K56 acetylation, and H2A-S129 phosphorylation in Beauveria bassiana

Abstract: Histone acetyltransferases and deacetylases maintain dynamics of lysine acetylation/deacetylation on histones and nonhistone substrates involved in gene regulation and cellular events. Hos2 is a Class I histone deacetylases that deacetylates unique histone H4-K16 site in yeasts. Here, we report that orthologous Hos2 deacetylates H4-K16 and is also involved in the acetylation of histone H3-K56 and the phosphorylation of histone H2A-S129 and cyclin-dependent kinase 1 CDK1-Y15 in Beauveria bassiana, a filamentous… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
39
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 26 publications
(42 citation statements)
references
References 57 publications
3
39
0
Order By: Relevance
“…This observation is in accordance with results from yeast, where HOS2 was shown to shuttle between the cytoplasm and the nucleus via a chaperone dependent process ( Liu et al, 2012 ). Moreover, during the preparation of this manuscript, a paper was published that presented clear evidence that a HosA ortholog in the insect-pathogenic fungus Beauveria bassiana is indirectly involved in both, global acetylation and phosphorylation of H3K56 and H2AS129, respectively, providing further evidence of an indirect effect of HosA-type proteins in the regulation of fungal transcription via deacetylation of HATs or kinases ( Cai et al, 2018 ).…”
Section: Discussionmentioning
confidence: 99%
“…This observation is in accordance with results from yeast, where HOS2 was shown to shuttle between the cytoplasm and the nucleus via a chaperone dependent process ( Liu et al, 2012 ). Moreover, during the preparation of this manuscript, a paper was published that presented clear evidence that a HosA ortholog in the insect-pathogenic fungus Beauveria bassiana is indirectly involved in both, global acetylation and phosphorylation of H3K56 and H2AS129, respectively, providing further evidence of an indirect effect of HosA-type proteins in the regulation of fungal transcription via deacetylation of HATs or kinases ( Cai et al, 2018 ).…”
Section: Discussionmentioning
confidence: 99%
“…This process has been evidently associated with the functions of many genes characterized in B. bassiana, such as those encoding the histone acetyltransferases Gcn5 and Mst2 (7, 9), the histone deacetylases Hos2 and Rpd3 (10, 11), the mitogen-activated protein kinase (MAPK) kinase Ste7 (12), the Na + /H + antiporter Nhx1 (13), the blue-light photoreceptor VVD (6), the vacuolar protein VLP4 (14) or ATPase subunit H VmaH (15), the lysyl-tRNA synthetase KRS (16), and the cyclophilin B CypB (17). Interestingly, these studied genes are also responsible for a correlation of dimorphic transition in vitro or in vivo with aerial conidiation and transcriptional activation of key activator genes in the central development pathway, as summarized in Table 1.…”
Section: Introductionmentioning
confidence: 99%
“…Phenotype assays suggested that in A. niger FGSC A1279, HosA played the most important role in the phenotype, including hyphal growth, pigment accumulation, and spore count of eight histone deacetylases. In Beauveria bassiana , deletion of hos2 increased the sensitivity to oxidative stress and reduced conidiation capacity [33]. The synthesis of SMs and proteins involved in virulence and disease are significantly affected by the deletion of HosA [34].…”
Section: Discussionmentioning
confidence: 99%
“…In addition to being linked to histone deacetylation, HosA may be responsible for other epigenetic modifications. In Beauveria bassiana , the histone deacetylase Hos2 plays an indirect role in acetylating H3-K56 and phosphorylating H2A-S129 [33].…”
Section: Discussionmentioning
confidence: 99%